2019
DOI: 10.7554/elife.45919
|View full text |Cite
|
Sign up to set email alerts
|

PIE-scope, integrated cryo-correlative light and FIB/SEM microscopy

Abstract: Cryo-electron tomography (cryo-ET) is emerging as a revolutionary method for resolving the structure of macromolecular complexes in situ. However, sample preparation for in situ Cryo-ET is labour-intensive and can require both cryo-lamella preparation through cryo-focused ion beam (FIB) milling and correlative light microscopy to ensure that the event of interest is present in the lamella. Here, we present an integrated cryo-FIB and light microscope setup called the Photon Ion Electron microscope (PIE-scope) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 30 publications
(42 reference statements)
0
91
0
Order By: Relevance
“…It is well-known that fluorescent dyes can be quenched when in close proximity of gold particles [110]. We have recently shown that Alexafluor488 coupled to a 10 nm gold particle is quenched by 95% [111] rendering that particular probe useless as a true CLEM probe. One is probably better off using two individual probes, one tagged with fluorescence and one tagged with gold particles.…”
Section: Clem and Correlative Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…It is well-known that fluorescent dyes can be quenched when in close proximity of gold particles [110]. We have recently shown that Alexafluor488 coupled to a 10 nm gold particle is quenched by 95% [111] rendering that particular probe useless as a true CLEM probe. One is probably better off using two individual probes, one tagged with fluorescence and one tagged with gold particles.…”
Section: Clem and Correlative Microscopymentioning
confidence: 99%
“…Fully integrated light and electron microscopes should be able to provide the best correlation between the two modalities and both integrated LM-TEM [151] and LM-SEM [111,152] have been developed and are still improving. Of note here is that all these systems can only work with fixed samples and one of the hallmarks of light microscopy, live imaging, is lost.…”
Section: Clem and Correlative Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…However, technical challenges remain in ensuring that the milled lamellae contain the features of interest. Correlative light and electron microscopy (CLEM) can overcome this challenge by fluorescently labelling targets 7,8 , thereby guiding cryoFIB-SEM milling 9,10 and the selection of optimal imaging areas for cryoET experiments, as well as aiding the interpretation of observed features. However, even the smallest eukaryotic cells are typically several microns thick and the desirable lamella thickness range is ∌100-500 nm; thus, targeting nanoscale features along the z direction remains extremely challenging.…”
Section: Introductionmentioning
confidence: 99%
“…This not only results in an elevated cost, but it also restricts production to a throughput 59 of 5-10 lamellae per day (Danev, One way to counteract the low throughput of cryo-lamella preparation consists of targeting a region 74 based on the known presence of an interesting event or structure. In order to achieve this level of 75 efficiency, the typical approach uses correlative light and electron microscopy techniques which, when 76 properly performed, prevents from imaging areas that do not contain useful information for a specific 77 study (Arnold et al, 2016;Gorelick et al, 2019). Regardless of the correlative microscopy approach in 78 use, the mismatch between the throughput of cryo-ET and the preparation of lamellae is evident.…”
Section: Introduction 29mentioning
confidence: 99%